Rapid expansion in the WAVE bioreactor of clinical scale cells for tumor immunotherapy - Yiming Meng; Jing Sun; Tingting Hu; Yushu Ma; Tiaozhao Du; Cuicui Kong; Guirong Zhang; Tao Yu; Haozhe Piao (Taylor & Francis Group, 2018)
Cell-based immunotherapy using natural killer (NK) cells, cytokine-induced killer (CIK) cells and dendritic cells (DCs) is emerging as a potential novel approach in the auxiliary treatment of a tumor. However, non-standard operation procedure, small-scale cell number, or human error may limit the clinical development of cell-based immunotherapy. To simplify clinical scale NK cells, CIK cells and DCs expansions, we investigated the use of the WAVE bioreactor, a closed system bioreactor that utilizes active perfusion to generate high cell numbers in minimal volumes. We developed an optimized rapid expansion protocol for the WAVE bioreactor that produces clinically relevant number of cells for our adoptive cell transfer clinical protocols. The high proliferative rate, surface phenotypes, and cytotoxicity of these immune cells, as well as the safety of cultivation were analyzed to illuminate the effect of WAVE bioreactor. The results demonstrated that the benefit of utilizing modern WAVE bioreactors in cancer immunotherapy was simple, safe, and flexible production.